NATIONAL-CULTURAL AND PRAGMATIC FEATURES OF EUPHEMISMS AND POLITICAL CORRECTNESS IN REPRESENTING SOCIALLY DISADVANTAGED GROUPS IN UZBEK - Jabborova Aziza Jobirovna (Journals Park Publishing, 2025)
This study examines the national-cultural and pragmatic features of euphemisms and politically correct expressions used to represent socially disadvantaged groups in the Uzbek language. Drawing on a corpus of media texts, governmental documents, and public discourse, the research explores how lexical choices, politeness strategies, and cultural norms influence the way sensitive social categories-such as people with disabilities, low-income communities, and marginalized minorities-are described. The findings demonstrate that Uzbek employs a rich set of culturally embedded euphemisms that reflect traditional values of respect, collectivism, and social harmony. Pragmatically, the discourse reveals strong tendencies toward face-saving strategies, indirectness, and the avoidance of explicit negative labeling. These linguistic patterns not only soften socially sensitive references but also reinforce cultural ideals of dignity and inclusivity. The study concludes that euphemisms and political correctness in Uzbek are shaped by both evolving global norms and deeply rooted national-cultural frameworks, highlighting the need for greater linguistic transparency and sensitivity in public communication.
Keywords: Euphemism; political correctness; Uzbek language; socially disadvantaged groups; national-cultural features; pragmatic strategies; politeness; face-saving; discourse analysis.